Penerapan Senam Aerobik untuk Menurunkan Gejala Menopause pada Wanita Menopause - Yeskia Aprinda.P; M.K Fitriani Fruitasari; Srimiyati Srimiyati (Jurnal Ventilator, 2024)
Along with getting older, women will experience a developmental process so that there will be changes experienced by every woman. These changes can occur due to the aging process and of course every woman will experience a menopause phase. One of the Evidence Based Practices of Nursing that has been implemented and is popular among the community, especially women, is aerobic gymnastics. The aim of this application is to reduce menopausal symtoms in menopausal women. This method of application uses one group pretest and posttest on 3 menopausal female clients. The results of the application were obtained in clients 1 and 2 experienced a decrease in MRS scores but still remained in the interpretation of moderate symptoms and client 3 experienced a decrease in MRS scores from interpretation of severe symptoms to moderate symptoms. The application of aerobic gymnastics can reduce menopausal symptoms in 1 menopausal woman in RT 27 Sukarami Village because through gymnastics there are increased metabolic changes but physical activity will generally be more effective if done for 3 months to get more effective results. This application is expected to help menopausal women to reduce menopausal symptoms.